Optimization of photocatalytic degradation of malachite green using nano-scaled V/CeO2-functionalized steel-slag-based catalyst by response surface design approach - Hao Zhang; Sifan Liu; Kai Wang; Haoqi Huang; Fan Zhang; Le Kang (Journal of Materials Research and Technology, 2023)
The utilization of steel slag with high added value is an important means for sustainable development of the iron and steel industry and environment. A new nano-scaled V/CeO2-functionalized steel-slag-based catalyst (V/CeO2-SC) was prepared. The XPS results revealed that V was embedded in the CeO2 lattice with V4+ and V5+ forms. The regression equation analysis of variance told that the order of influencing factors on malachite green dye degradation rate is: catalyst dosage > V doping amount > malachite green dye concentration. The optimum values of the parameters were dye concentration 10 mg/L, catalyst dosage 0.1 g, and V doping amount 1wt%. Under the optimal condition, the predicted and actual response values of the degradation rate of malachite green dye were 100.00%. UV–Visible light absorption spectroscopy results demonstrated that after the photocatalytic degradation reaction, the absorption peak of the malachite green dye solution almost completely disappeared, indicating that the malachite green dye solution was almost completely degraded. The excellent degradation activity of the 1V/CeO2-SC specimen was attributed to the co-action of the high SBET, large mesoporous volume, and the coupled semiconductors formed by V-doped CeO2 and FeO in the catalyst carrier. A possible photocatalytic degradation mechanism of the V/CeO2-SC specimen was proposed.